Comparative analysis of the use of fertilizers by EU countries and Ukraine in the context of the development of agrobiotechnologies - Omelych, I.Yu.; Neposhyvailenko, N.O. (Problems of Environmental Biotechnology, 2023)
According to Eurostat data, the total area of organic farming in the territory of the European Union has grown rapidly in recent years. In Ukraine, according to the data of the State Statistics Service, the growth of organic farming is also observed. At the same time, the level of consumption of mineral fertilizers remains high both in the EU member states and in Ukraine. It is known that mineral fertilizers are one of the sources of heavy metals entering the soil. Therefore, the transition to organic farming with the use of biofertilizers will help to reduce the accumulation of heavy metals in the soil.